Rationale of Optic Nerve Decompression in Optic Nerve Injury - Mahapatra, AK (Indian Journal of Neurotrauma, 2004)
Optic nerve injury following closed head injury is uncommon and reported in 1-5% cases. Interestingly, incidences as high as 44% was reported by Crompton, among them 20% had bilateral pathologies. Surprisingly only few large series has been published in the World literature. Most of the published series are retrospective analysis of smaller number of cases. We at AIIMS have prospectively analyzed a large number of patients with optic nerve injury over the last 2 decades & rationalized the protocol, based on our experience including indications for optic nerve decompression. Thus this publication is based on the experience of 800 patients of optic nerve injury, treated between 1983-2002.
Keywords: Optic nerve injury; Head injury; Rationale of optic nerve decompression; outcome